A Comparative Study of Electrical Characterization of P-Doped Distributed Bragg Reflectors Mirrors for 1300 nm Vertical Cavity Semiconductor Optical Amplifiers - Chaqmaqchee, Faten A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
This paper presents an electrical analysis of various diameters of two p-types of GaAs/Al0.9Ga0.1As and two p-types of GaAs/Al0.3Ga0.7As/Al0.9Ga0.1As distributed Bragg reflectors (DBRs) mirrors structure grown on undoped and on p-doped GaAs, which affects the characteristics of 1300 nm vertical cavity surface emitting lasers (VCSELs) and vertical cavity semiconductor optical amplifiers (VCSOAs). Electrical characterizations and Hall measurements of current−voltage (IV) for GaAs/Al0.9Ga0.1As linear DBRs and GaAs/Al0.3Ga0.7As/Al0.9Ga0.1 As graded DBRs were also performed at temperatures between 13 and 300 K. Consequently, p-type DBRs are designed with graded composition interfaces technique. The smaller mesa diameters are used to reduce vertical and longitudinal resistances and to limit the heating effect and improve the characteristics of VCSEL/VCSOA devices.